Peran Kepala Desa Yang Berkualitas Dalam Meningkatkan Kapasitas Perangkat Desa Dan Staf Di Desa Untang Kec. Banyuke Hulu Kab. Landak Propinsi Kalimantan Barat - Martinus Mela; Sri Sundari (International Forum of Researchers and Lecturers, 2024)
This study discusses, in general, the role of the village leader in efforts to increase the capacity of village devices. Enhancement or development of the capacity of the village equipment is carried out by the village head through the implementation of education and training. The research carried out included qualitative descriptive research. The object of this research is the Head of Untang Village Office, Banyuke Hulu District, Landak, West Kalimantan Province. The results of the research show that the role of the village chief in trying to increase the capacity of the villages has been very good. The activities carried out by the village chief as an attempt to develop capacity towards the village devices are direct observation of the performance of the village equipment, direct guidance, procurement of training related to administrative governance, and the use of information technology. The efforts made by the village chief can improve the competence or capacity of the village unit, thus having an impact on the fulfillment of the tasks and responsibilities assigned as well as the services rendered to the community.